Advances in the molecular diagnosis of diffuse large B-cell lymphoma in the era of precision medicine. (2nd October 2016) - Araf, Shamzah; Korfi, Koorosh; Rahim, Tahrima; Davies, Andrew; Fitzgibbon, Jude
ABSTRACT: Introduction: The adoption of high-throughput technologies has led to a transformation in our ability to classify diffuse large B-cell lymphoma (DLBCL) into unique molecular subtypes. In parallel, the expansion of agents targeting key genetic and gene expression signatures has led to an unprecedented opportunity to personalize cancer therapies, paving the way for precision medicine. Areas covered: This review summarizes the key molecular subtypes of DLBCL and outlines the novel technology platforms in development to discriminate clinically relevant subtypes. Expert commentary: The application of emerging diagnostic tests into routine clinical practise is gaining momentum following the demonstration of subtype specific activity by novel agents. Co-ordinated efforts are required to ensure that these state of the art technologies provide reliable and clinically meaningful results accessible to the wider haematology community.